The effect of job demands, job resources, and job satisfaction towards work engagement - Nur Farihah, Fadzil (2017)
Work engagement among the employees is very essential to ensure the maximum organization performance and employees providing an excellent service to their customers.Due to that, several factors that influences work engagement are given priority in this research. This study investigated the direct relationship between job demands (work pressure, workload, and workfamily conflict), job resources (social support, performance feedback and career opportunity), job satisfaction and work engagement.A total of 327 questionnaires were personally distributed to the respondents in Police Headquarters Contingent within Northern areas which are Penang, Kedah and Perlis. From the 327 questionnaires distributed, 167 questionnaires were returned, representing a response rate of 51%. The results for direct relationship showed that work-family conflict and career opportunity is negatively related to work engagement, while work pressure, workload, social support and performance feedback were positively related to work engagement. The results also showed that job satisfaction was positively related to work engagement. In conclusion, based on this research that job demands, job resources and job satisfaction give direct effect towards work engagement among police officers’ based on the nature of their jobs.